Optimization of Real-Time Quantitative PCR assay for detection of Echinococcus granulosus in fecal samples - Tahvildar Biderouni, Farid; Jalousian, Fateme; Hosseini , Seyed Hossein; Soltani, Minoo; Yeganeh, Farshid (Novelty in Biomedicine, 2022)
Background: Echinococcosis/hydatidosis is one of the most important zoonotic diseases. The definitive hosts for Echinococcus granulosus (E. granulosus) include a wide variety of the Canidae and dogs. Early detection of Echinococcosis in dogs is the most influential factor in improving the prevention and control of hydatidosis. The primary purpose of the present study was to optimize the real-time quantitative PCR to diagnose E. granulosus infection in dogs before the disposal of eggs. Materials and Methods: Three puppies were selected to be inoculated by 70000 protoscoleces. Normal saline was inoculated to the other two puppies chosen as an experimental negative control group. Ten privately owned healthy puppies were selected for the natural negative control group. Stool samples were collected on days 7, 14, 21, 28, and 35 post-infection, DNA was extracted, then a 287bp fragment of tandem repeat region gene was amplified and cloned into linearized TA vectors. Serial dilutions of recombinant plasmid DNA and a standard curve were established. The copy amount of DNA in each sample was determined based on the standard curve. Results: The minimum time copro –DNA could be detected in the stool sample was found on the 7th day post-infection, which was equal to 9750×10-8 copy number or 9.75 pg of DNA. The assay was linear in 105 to 108 copies of the recombinant plasmid per microliter. Conclusion: The real-time PCR assay diagnosed the infection eight days earlier than the copro antigen ELISA method (7 days versus 15 days, respectively). Conclusion: The real-time PCR assay diagnosed the infection eight days earlier than the copro antigen ELISA method (7 days versus 15 days, respectively).